2012
DOI: 10.4172/2161-0509.1000115
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Intake among Children with Autism

Abstract: The objective of this study was to examine adequacy of nutrient intake and determine the impact of multivitamin use on nutrient intake in children with autism. This was a retrospective analysis of food frequency questionnaire data collected from 54 children, ages 2-8 years, in the Autism Integrated Metabolic and Genomic Endeavor Study at Arkansas Children's Hospital Research Institute, Little Rock, AR. The average percent of Kilocalories from carbohydrate, protein and fat fell within the acceptable macronutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Results for macronutrient intake in children with ASD essentially mirror results found in multiple other studies [5,9,10,11,15]. Children met or exceeded recommendations for protein and carbohydrate intake, though based on the excessive protein and carbohydrate intake, the calculated percentage of dietary fat intake is slightly lower than recommended.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Results for macronutrient intake in children with ASD essentially mirror results found in multiple other studies [5,9,10,11,15]. Children met or exceeded recommendations for protein and carbohydrate intake, though based on the excessive protein and carbohydrate intake, the calculated percentage of dietary fat intake is slightly lower than recommended.…”
Section: Discussionsupporting
confidence: 69%
“…Calcium, magnesium, iodine, and potassium intake were insufficient for the majority of subjects. Moore et al report similar findings, with intake below DRIs for calcium, potassium, vitamin D, and vitamin E [10]. Xia et al reported that DRI requirements for Vitamins A, B6, C, folic acid, calcium, and zinc were not met in their study of 111 children between ages 2 and 9 years [9].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Inflammation [ 120 , 121 ], gastrointestinal issues [ 123 , 124 ], antiepileptic drugs [ 125 ] and genetics are among these factors. Furthermore, children with ASD may receive less sunlight due to lower outdoor activity and have inadequate intake of vitamin D [ 114 , 118 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 ], i.e. , reverse causality.…”
Section: Three Major Areas Of Researchmentioning
confidence: 99%
“…Nutrition screening must go beyond collecting anthropometric data on the children. We previously reported, children may plot within the normal ranges on growth charts yet still have micronutrient deficiencies [7]. Therefore, dietary intake must be considered by including standard questions that screen for dietary adequacy.…”
mentioning
confidence: 99%